Analysis of the Factors Affecting the Adoption of GIS/LIS in Birnin Kebbi, Kebbi State, Nigeria - Saidu, B. B.; Bawa, C. A. (International Journal of Real Estate, 2025)
The adoption of Geographic Information Systems (GIS) and Land Information Systems (LIS) is crucial for effective land administration and governance. This study investigates the factors influencing GIS/LIS adoption in Kebbi State, Nigeria, focusing on the role of the Geographic Information System Agency (KEBGIS). Using a combined theoretical framework that integrates the Theory of Planned Behavior (TPB), the Technology Acceptance Model (TAM), and the Diffusion of Innovation Theory (DOI), the study identifies key determinants of adoption, including perceived usefulness, ease of use, organizational support, and personal innovativeness. Data were collected through a structured questionnaire administered to 102 participants across various government ministries and land-related organizations. Structural equation modeling revealed that attitudes, perceived behavioral control, and personal innovativeness significantly influence adoption intentions, while subjective norms play a limited role. Key barriers identified include inadequate infrastructure, skill gaps, financial constraints, and resistance to change. The study recommends targeted awareness campaigns, enhanced organizational support, capacity building, and fostering personal innovativeness to improve adoption rates. These findings provide valuable insights for policymakers and stakeholders in developing robust land administration systems in Nigeria and similar contexts.